IMPROVING STUDENTS WRITING SKILL THROUGH HANDS ON ACTIVITY METHOD IN CLASS 3 SDN 1 SUKARAJA SUKABUMI - Santris Muhammad Tegar; N Erni Susanti; Atik Mulyati; Ruli Setiyadi (COLLASE (Creative of Learning Students Elementary Education), 2018)
The research entitled Improving Students Writing Skill Through Hands On Activity Method In Class 3 SDN 1 Sukaraja Sukabumi was motivated by the decrease of children's ability in writing due to the lack of teacher's attention to students' writing ability. In addition, learning strategies used by teachers are still there weaknesses and shortcomings. The method used in this study is descriptive qualitative method by comparing the learning outcomes of children before and after treatment. This research was conducted at SDN 1Sukaraja in Sukabumi area. The result of this research is the increase of children writing ability as much as 73%. It can be said that Hands On Activity method can help improve the literacy ability of children especially in writing ability